Effect of Turbocharger Upgrade on the Energy Economy of a Medium Speed Engine - Istolahti, Miia (My University, 2019)
Engine lifecycle can be supported by offering regular overhaul service or by upgrading parts to new versions. Part upgrade can aim e.g. to better engine energy efficiency and lower emissions. Background of an upgrade is usually the possibility to utilize new product features in an operating engine. To get the upgrade profitable the payback period needs to be short enough. Upgrade of an engine turbocharger can aim, among other targets, to emission reduction or savings in fuel oil consumption. Fuel oil consumption reduction of realized turbocharger upgrades have been up to 3 %. During the upgrade Miller timing is added if it already has not been utilised. Testing of turbocharger upgrade in a field engine is expensive, thus simulation is seen as a good alternative. The purpose of this work was to develop a GT-Power model for a medium speed engine where Miller timing was not used. The finished model was used to investigate turbocharger upgrade possibilities with Miller timing. Turbine and compressor were replaced, and valve timing was modified. Target of the upgrade was to achieve 4 g/kWh savings in specific fuel oil consumption (SFOC). However, the target was not reached. It was stated that the project is not profitable to carry out with a real engine. Further study of the effects of more advanced Miller timing on SFOC is recommended. With the upgraded model, ambient temperatures of 5-45°C and altitudes of 1000 and 2000 meters were simulated. The model worked as expected and results were following well the trends of rules of thumb. It was stated that the model can be used in the future to investigate turbocharger upgrade of the engine type. Heat release rate should be revised to guarantee correct results.
Keywords: Diesel engine; turbocharger upgrade; camshaft upgrade; Miller timing; SFOC savings; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|